Diagnosis and Treatment of Sepsis in a Fourteen-year-old Patient: A case study of pulmonary inflammatory discharge without typical features of respiratory tract infection - Bartłomiej Żaczek; Jakub Kozłowski; Alicja Kamińska; Wojciech Kupczak; Kinga Bujak; Aleksandra Kocjan; Ismael Alsoubie; Natalie Papachristoforou; Wojciech Kaźmierski; Mateusz Ziomek; Paulina Lis; Marta Czubaj-Kowal (Journal of Education, Health and Sport)
Introduction and aim. Sepsis is a set of symptoms caused by the body’s uncontrolled inflammatory response to infection, leading to damage to more than one organ and homeostasis disorders. Symptoms of sepsis in children may be non-specific, making it difficult to diagnose quickly and effectively.